Expression, Purification, and Characterization of Aspergillus fumigatus Sterol 14-α Demethylase (CYP51) Isoenzymes A and B - Warrilow, Andrew G. S. (American Society for Microbiology (ASM), 2010)
Aspergillus fumigatus sterol 14-α demethylase (CYP51) isoenzymes A (AF51A) and B (AF51B) were expressed in Escherichia coli and purified. The dithionite-reduced CO-P450 complex for AF51A was unstable, rapidly denaturing to inactive P420, in marked contrast to AF51B, where the CO-P450 complex was stable. Type I substrate binding spectra were obtained with purified AF51B using lanosterol (K(s), 8.6 μM) and eburicol (K(s), 22.6 μM). Membrane suspensions of AF51A bound to both lanosterol (K(s), 3.1 μM) and eburicol (K(s), 4.1 μM). The binding of azoles, with the exception of fluconazole, to AF51B was tight, with the K(d) (dissociation constant) values for clotrimazole, itraconazole, posaconazole, and voriconazole being 0.21, 0.06, 0.12, and 0.42 μM, respectively, in comparison with a K(d) value of 4 μM for fluconazole. Characteristic type II azole binding spectra were obtained with AF51B, whereas an additional trough and a blue-shifted spectral peak were present in AF51A binding spectra for all azoles except clotrimazole. This suggests two distinct azole binding conformations within the heme prosthetic group of AF51A. All five azoles bound relatively weakly to AF51A, with K(d) values ranging from 1 μM for itraconazole to 11.9 μM for fluconazole. The azole binding properties of purified AF51A and AF51B suggest an explanation for the intrinsic azole (fluconazole) resistance observed in Aspergillus fumigatus.